Registration of 'Saluki 4910' Soybean [Glycine max (L.) Merr.] with High Yield Potential and Resistance to Multiple Diseases. Issue 1 (16th October 2012) - Kantartzi, Stella K.; Klein, James; Schmidt, Michael
Abstract : 'Saluki 4910' (Reg. No. CV‐507, PI 665035) soybean [ Glycine max (L.) Merr.] was developed at Southern Illinois University, Carbondale, IL, and released in May 2010. The objective was the development of a line with high yield and resistance to the important diseases soybean cyst nematode (SCN) and sudden death syndrome (SDS; caused by Fusarium virguliforme O'Donnell & T. Aoiki, sp. nov.). Saluki 4910 is an F5 selection from the cross of 'Pana' and TN96‐58 that advanced from the F2 generation by the modified single‐seed descent method. It is a late maturity group IV (relative maturity 4.9) soybean line that was tested for yield and multiple agronomic traits in four locations in southern Illinois and 14 field environments in the Uniform MG IV‐S Tests, Southern States. In combined analyses across 3 yr (2006–2008) in southern Illinois, Saluki 4910 (LS03‐4294) averaged 3977 kg ha −1, which was 5.9% more than '5R531' and 9.6% more than 'Manokin'. In the Uniform MG IV‐S Tests, Southern States, the yield of Saluki 4910 averaged 3539 kg ha −1, which was 11.4% better than '5002T', 4.8% better than 'AG 4403', 1.9% better than 'AG 4903', and 3.8% better than 'DK 4844'. In the Southern Illinois University SDS and frogeye leaf spot (FLS; caused by Cercospora sojina Hara) trials, Saluki 4910 showed high resistance to both diseases. Additionally, in the USDA Southern Preliminary and Uniform tests, the line showed high resistance to SCN HG Type 0 (Race 3) and stem canker [caused by Diaporthe phaseolorum (Cooke & Ellis) Sacc.], . Saluki 4910 was released because of its usefulness for production in the Midwest due to its competitive yield, relatively high protein content, and resistance to SCN HG Type 0 (Race 3), SDS, FLS, and stem canker, and as a parental line in soybean breeding programs.